PENGARUH SELF EFFICACY DAN MOTIVASI TERHADAP KESIAPAN KERJA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNJANI - Dian Lestari; Aam Rachmat Mulyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Final year students must really prepare themselves to enter the world of work. To be able to compete in the world of work, students must present themselves as well as possible. This research was conducted to determine the influence of self-efficacy and motivation on work readiness of final year FEB Unjani students. This research using quantitative approach and an explanatory survey, which is used to explain the effect between variables. The respondents of this research were final semester students of the Faculty of Economics and Business, Unjani. Data is collected by questionnaire and techniques of data analysis uses multiple regression analysis, where the classical assumptions are tested first. Hypothesis testing uses the t test and F test. From t test founds that self efficacy has a positive effect on work readiness of final year FEB Unjani students, so does motivation variable. And from the f test founds that self efficacy and work motivation effect simultaneously on work readiness of final year student in FEB Unjani.